STABILISASI TANAH LEMPUNG MENGGUNAKAN SEMEN DAN KAPUR UNTUK MENINGKATKAN DAYA DUKUNG CBR TANAH - Miswar Miswar; Syaifuddin Syaifuddin; Neilul Amani (Portal: Jurnal Teknik Sipil, 2017)
Land is a very influential material in a road construction work. Soil has properties that can interfere with a road construction such as relatively large shrinkage and low CBR values. One of the land improvement efforts under study is stabilization using cement and lime. The objectives of this study were to compare the clay CBR values before and after stabilization with the addition of cement and lime respectively 0%, 6%, 12% and 18% based on dry soil weight with a period of 4 days. Tests cover physical and mechanical properties of soil compaction and CBR Laboratory by referring to SNI for each test. The result of the unsoaked CBR testing was 18.2% after 4 days of curing there was an increase of 184.4% in 18% cement addition and 21.0% in the addition of 18% lime and the soaked CBR testing was 6.1% after being soaked for 4 days There was a 157.8% increase in cement 18% and 17.3% increase in the addition of 18% chalk. Cement and lime form a binding material resulting in an increase in the value of CBR. The use of cement and lime can increase the carrying capacity of clay soils as the percentage of cement and lime increases.Keywords: clay soil, cement and lime, CBR.